Effect of Various Chemical Herbicides on Nutrient uptake, Yield Attributes and Economics of Maize (Zea mays L.) - Kumar, Arvind; Tomar, S. S.; Verma, V. K.; Kumar, Abhinav; Singh, R. K. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted to assess the effect of chemical herbicides on nutrient uptake, yield and economics of maize (Zea mays L.) maize during kharif season of 2013 at the Crop Research Centre, Chirori of Sardar Vallabhbhai Patel University of Agriculture and Technology; Meerut, Uttar Pradesh (India). The results revealed that the among chemical methods of weed control, the maximum uptake of N and P in maize grains was observed with Alachlor+Metribuzin @ 750+375 g ha-1 (T6) and the maximum K uptake by maize grains was observed with Atrazine+Pendimethalin @ 750+500 g ha-1 (T7) and maximum N, P and K uptake in maize stover was observed with Atrazine+Pendimethalin @ 750+500 g ha-1 (T7) along with grain yield (q ha-1), stover yield (q ha-1) as well as harvest index, respectively. The minimum uptake of N, P and K in maize grain and stover was observed under weedy check along with grain yield (q ha-1 ), stover yield (q ha-1) as well as harvest index, respectively. Protein content in maize grain found highest in weed free (T11) (8.7%). The higher dry weight, NPK content and uptake by weed under Atrazine+2, 4-D @ 500+500 g ha-1 (T8) and the higher weed index was found under Sesbania (BC)+2,4-D @ 500 g ha-1 30 DAS (T9) treatment. The higher gross return, net return and B:C ratio was observed under Atrazine+Pendimethalin @ 750+500 g ha-1 (T7). These values were very close to weed free treatment. The per cent increase in grains and stover yield was to the tune of 107.14 and 57.26 as compared to weedy check.